Paleoecology of Albian – Santonian succession of Surdash to Shaqlawa area, NE Iraq - A. Hussain, Salah; AL-Sheikhly, Saad S. (Iraqi Journal of Science, 2023)
Three formations to be studied along Surdash, Qallat, Khalakan, Hezob, Sektan, Degalaand Shaqlawa areas in the Sulaimaniya and Erbil governorates, NE Iraq. These are: Dokan,Gulneri and Kometan formations. The paleoecology and depositional environment of theseformations are determined by studying the ecology of the planktonic and benthicforaminifera.The depositional environment of are ranged from the continental shelf to the abyssal,and the paleotemperature, salinity and paleoclimate were discriminated in each sectionalong the study area.